Pengaruh Metode Talaqqi Terhadap Kemahiran Dalam Membaca Al-Qur’an Santri Kelas A Tahsin Pondok Pesantren Al-Qur’an Nurul Furqon Cibinong Bogor - Anam, Am Irsaddul (Edusifa: Jurnal Pendidikan Islam, 2022)
This study aims to increase enthusiasm in learning the Qur'an through the Talaqqi Method. The problem of this study aims to determine how much influence the learning method using the Talaqqi Method has in reading the Qur'an in a case study of class A Tahsin Pondok Pesantren Al- Qur'an Nurul Furqon Cibinong Bogor. The population in this study were students of the Al-Qur'an Nurul Furqon Islamic boarding school for the 2021 academic year, but only 29 people were sampled in class A Tahsin Al-Qur'an Pondok Pesantren Nurul Furqon. The results of the description analysis revealed that the effect of the Talaqqi method was on a strong result (Mean 40.71%) and the value of the students' reading ability of the Qur'an was (59.29%) while the correlation was 0.77% which lies between 0.78% is included in the strong category. The results of the coefficient of determination show that the Talaqqi Method has an impact on the ability to read the Qur'an by 59.29% and the remaining 40.71% is influenced by other factors not examined. These results reveal a positive influence on students' proficiency in reading the Qur'an. Thus, the results of this study can be concluded that the Talaqqi Method is quite good for proficiency in reading the Qur'an. Case study of class A students Tahsin Islamic boarding school Al-Qur'an Nurul Furqon Cibinong Bogor Keywords: Effect of Talaqqi Method, Improving Proficiency, Reading Al-Qur'an